2017
DOI: 10.1111/scs.12552
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning evaluated by family members of older patients and nurses in emergency departments

Abstract: The functioning of families in emergency departments (EDs) encompasses the level at which the families of older patients perform as a whole during the ED stay. Currently, little is known about how the families of older patients function in EDs. In this study, family functioning included the subareas of family strengths, structural factors and relationships both inside and outside the family. The study aimed to describe family functioning in EDs as evaluated by both the family members (n = 111) of older patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…This study found that family functioning was moderately and positively associated with life satisfaction, which confirmed that a higher familial sense of togetherness, familiarity, and satisfaction with family ties contributed to improved psychological wellbeing for stroke patients when they faced a public health emergency ( 21 , 45 ). Most research has shown that people who have stronger familial cohesion and communication have more positive perceived family roles and responsibilities, and thus, higher life satisfaction ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 61%
“…This study found that family functioning was moderately and positively associated with life satisfaction, which confirmed that a higher familial sense of togetherness, familiarity, and satisfaction with family ties contributed to improved psychological wellbeing for stroke patients when they faced a public health emergency ( 21 , 45 ). Most research has shown that people who have stronger familial cohesion and communication have more positive perceived family roles and responsibilities, and thus, higher life satisfaction ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, the participants who lived alone described feeling insecure and anxious when home alone and were concerned about being unable to call for help due to acute illness. Demidenko et al described how essential it is for health professionals working in an ED to know the level of support and understand a family's functioning [39]. Living alone and weak social relationships are associated with a higher risk and frequency of unplanned hospitalisation among older adults [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…13 14 However, research on the needs of family members involved in short visits to EDs is sparse or focuses on elderly patients. 15 16 To date, little is known of how patients and families experience short-term stays in the ED and what needs and preferences they have. 17 18 In the interest of organising and practising tailored care, it is essential to explore the needs and preferences of patients and their family members to ensure that the care provided is valuable.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%